The Effect of Concentration of Skipjack Tuna (Katsuwonus pelamis) Powder and Drying Time on The Chemical Characteristics of Purple Sweet Potato (Ipomoea batatas L) Tortilla Chips - Ovdarlin Lahagu; Rachel Breemer; Syane Palijama (Universitas Pattimura, 2023)
Tortilla chips are a type of snack that contains high levels of carbohydrates compared to their protein content. So, tortilla chips need to be made with more local products from the area, like purple sweet potatoes and skipjack fish flour. The goal of this study was to find out what the effects of adding skipjack tuna (Katsuwonus pelamis) and the right amount of drying time are on the chemical properties of purple sweet potato (Ipomoea batatas L) tortilla chips and which treatment combinations work best. This study used a factorial RAL (completely randomized design) with two factors. The first factor was the concentration of skipjack fish powder (T), which had three treatment levels: T1 = 10%, T2 = 15%, and T3 = 20%. The second factor was drying time, which had two treatment levels: L1 = 6 hours and L2 = 7 hours. The results showed that tortilla chips with a concentration of 20% skipjack fish powder had the best results based on chemical characteristics, including 8,30% moisture content, 2,41% ash content, 0,36% fat content, and 73,59% carbohydrate content, a drying time of 7 hours had the best result based on chemical characteristics, including 8,04% moisture content, 2,60% ash content, 0,45% fat content, and 75,81% carbohydrate content; and the best treatment based on interaction was the fish powder with a concentration of 20% skipjack tuna and a drying time of 7 hours, which had a protein content of 15,41%.